Physiotherapy in Postoperative Recovery through Total Arthroplasty of Secondary Coxarthrosis - Silviu Gabriel Cioroiu (Editura Universitatii Transilvania din Brasov, 2023)
Total hip arthroplasty is a surgical intervention that replaces the affected joint with an artificial implant. This is recommended in case of damage to the targeted joint and the installation of acute pain. Currently, the procedure is most commonly performed in orthopedics, although results and patient satisfaction in the short or long term vary widely The purpose of the research is to restore the movement capacity of the lower limb following the operation through good documentation of the condition and the postoperative effects on the functioning mechanism at the articular level and by finding the kinetotherapeutic methods and means that correspond to an effective recovery.